ANALYSIS OF THE SUITABILITY OF BEACH TOURISM FOR RECREATION CATEGORY AT ANNAS DATOE BUTUNG BEACH, TANETE RILAU DISTRICT, BARRU REGENCY - Muhammad Alfa Rizki Nawawi; Amir Hamzah Muhiddin; Kamaruddin (Jurnal Ilmu Kelautan SPERMONDE, 2026)
This study aimed to examine the biophysical characteristics and evaluate the suitability of the coastal area for the development of recreational beach tourism in Tanete Rilau District, Barru Regency, South Sulawesi. The research was conducted from January to April 2026. The study area comprised three observation stations: Station 1, Station 2, and Station 3, each exhibiting distinct biophysical characteristics. The parameters observed included beach type, beach width, water substrate, depth, brightness, current speed, beach slope, land cover, presence of hazardous biota, and availability of freshwater. Data were collected through field surveys and analyzed using the Tourism Suitability Index (TSI). The results indicated that the TSI values at Stations 1 and 2 were 2.0 and 2.1, respectively, categorizing them as suitable, whereas Station 3 had a TSI value of 1.8, categorizing it as unsuitable. This suggests that Stations 1 and 2 possess potential for development as recreational beach tourism areas, while Station 3 is less suitable for tourism development.